All Days 2006
DOI: 10.2118/100753-ms
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Horizontal Wells in Gas Condensate Reservoirs: Hassi R'Mel Field, Algeria

Abstract: Hassi R'Mel Field is one of the biggest gas-condensate fields in the world. The southern area of this field, Module 02, has been depleted by vertical wells since 1979. Since 1981, water production has exceeded the allowed water limit. The salinity of the produced water is about 05 g/l, which is the maximum salinity allowed at the surface facilities. As a result, severe reservoir damage may have occurred. So the producing reservoir levels (C) were shut-in. The primary objecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…Goode introduced another horizontal model, different from Daviau’s model in that it assumed reservoir anisotropy ( K x = K y = K z ), which adopts the Daviau model while considering the inconsistency of permeability in the horizontal and vertical directions. , Ozkan utilized the Green function to address the pressure response of horizontal wells in homogeneous and dual-porosity reservoirs with horizontal wells, employing no-flow boundaries above and below, while also considering anisotropic reservoirs. Although Green functions and the Newman method had been developed by Gringarten and Ramey in 1973 to solve the problem of horizontal well unstable flow, their practical application has limitations, and it was not until 1991 that Ozkan and Raghavan introduced a comprehensive general solution based on Laplace variables. These models and solutions have guided the development and solution of various models of horizontal wells and have provided abundant spatial analytic models for single and corresponding fast calculation methods, greatly enriching theoretical models. Marir studied the horizontal PTA method for dual-porosity sealed oil reservoirs, but there were certain flaws in the pressure response solution, leading to significant errors in later-stage pressure calculations . Hashemi proposed that the superposition principle could be used to consider the effects of wellbore storage and skin factor on pressure response .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Goode introduced another horizontal model, different from Daviau’s model in that it assumed reservoir anisotropy ( K x = K y = K z ), which adopts the Daviau model while considering the inconsistency of permeability in the horizontal and vertical directions. , Ozkan utilized the Green function to address the pressure response of horizontal wells in homogeneous and dual-porosity reservoirs with horizontal wells, employing no-flow boundaries above and below, while also considering anisotropic reservoirs. Although Green functions and the Newman method had been developed by Gringarten and Ramey in 1973 to solve the problem of horizontal well unstable flow, their practical application has limitations, and it was not until 1991 that Ozkan and Raghavan introduced a comprehensive general solution based on Laplace variables. These models and solutions have guided the development and solution of various models of horizontal wells and have provided abundant spatial analytic models for single and corresponding fast calculation methods, greatly enriching theoretical models. Marir studied the horizontal PTA method for dual-porosity sealed oil reservoirs, but there were certain flaws in the pressure response solution, leading to significant errors in later-stage pressure calculations . Hashemi proposed that the superposition principle could be used to consider the effects of wellbore storage and skin factor on pressure response .…”
Section: Introductionmentioning
confidence: 99%
“…Marir studied the horizontal PTA method for dual-porosity sealed oil reservoirs, but there were certain flaws in the pressure response solution, leading to significant errors in later-stage pressure calculations. 17 Hashemi proposed that the superposition principle could be used to consider the effects of wellbore storage and skin factor on pressure response. 18 Baqawi introduced analytical solutions for hydraulic fractured horizontal wells in naturally fractured reservoirs, significantly improving calculation accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…There are only a few sensitivity studies which have discussed horizontal well performance in gas condensate reservoirs. Numerical simulations conducted by (Hashemi and Gringarten, 2005), (Dehane and Tiab, 2000), (Marir and Djebbar, 2006) and have all mainly been focused on the sensitivity of pertinent parameters on the performance of such wells.…”
Section: Introductionmentioning
confidence: 99%
“…Barnum et al (1995) reported that the higher the well capacity (well capacity is the kh product, where k is the rock permeability and h is the reservoir thickness, and is a measure of the reservoir quality), the less the impact of the condensate banking on the productivity of wells drilled in condensate reservoirs. Simulation and laboratory studies have indicated that condensate saturation around the wellbore may reach 70% (Marokane et al 2002).…”
Section: Introductionmentioning
confidence: 99%